2011
DOI: 10.1080/15426432.2011.619901
|View full text |Cite
|
Sign up to set email alerts
|

Why Child Welfare Supervisors Stay

Abstract: Research focusing on retention of child protection employees, primarily caseworkers, indicates that high turnover rates in child welfare agencies are a consequence of high levels of stress. A qualitative study was conducted utilizing a strengths perspective to explore the reasons that 50 child welfare supervisors remain employed, specifically whether retention was related to resilience or other personal characteristics. This article is excerpted from the larger study and discusses findings that indicate the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The second question aimed to identify the strategies that psychologists utilise to become more resilient. Previous research has found that an individual's strategies and attributes, such as coping skills, self‐care techniques, maturity, personality, perseverance, and using support services, are essential elements of resilience (Ausbrooks, ; D'Souza et al., ). We expanded on this finding and found many strategies that were adopted specifically by early‐career psychologists to boost their resilience levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second question aimed to identify the strategies that psychologists utilise to become more resilient. Previous research has found that an individual's strategies and attributes, such as coping skills, self‐care techniques, maturity, personality, perseverance, and using support services, are essential elements of resilience (Ausbrooks, ; D'Souza et al., ). We expanded on this finding and found many strategies that were adopted specifically by early‐career psychologists to boost their resilience levels.…”
Section: Discussionmentioning
confidence: 99%
“…Within a discipline related to psychology, Ausbrooks () conducted a study with child welfare supervisors and aimed to determine whether resilience would predict employee retention. This qualitative study found that those who were more resilient stated they were more likely to stay, and the key reasons for this appeared to be strengths in the form of perseverance, tenacity, follow‐through, coping skills, utilisation of support systems, self‐care techniques, and maturity gained from professional experience.…”
mentioning
confidence: 99%